2021
DOI: 10.2991/assehr.k.210407.284
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Fabel E-Comic in Bahasa Indonesia Lesson for Grade II of Elementary School

Abstract: The Development of Fabel E-Comic in Bahasa Indonesia Lesson for Grade II Of Elementary School. During online learning process in the era of covid-19, there is the lack of students understanding in reading learning process especially in looking for information from the text of fable and the lack of instructional media application from the teacher during learning process in Bahasa Indonesia class. It causes the students are not interested to the materials. Therefore, an instructional media that can make the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Digital comics are comics with simple picture stories in a series presented in electronic digital media (Y. F. Taufiq et al, 2020). Another opinion states that digital comics are digital-based electronic comics that can display the storyline and insert games, animations, films, and other applications so that readers can easily understand and appreciate each storyline and can be accessed online (Dwiasih & Agung, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Digital comics are comics with simple picture stories in a series presented in electronic digital media (Y. F. Taufiq et al, 2020). Another opinion states that digital comics are digital-based electronic comics that can display the storyline and insert games, animations, films, and other applications so that readers can easily understand and appreciate each storyline and can be accessed online (Dwiasih & Agung, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous research also stated that image media would make it easier for students to understand the subject matter (Dwiasih & Agung, 2021;Taufiq et al, 2020). Other research findings also state that media presented with the characteristics of teaching materials and students will make it easier for students to learn so that it has an impact on increasing student learning outcomes (Aggleton, 2019;Enteria & Casumpang, 2019;Ntobuo et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Digital comic media could be developed and suitable for use (Hobri et al, 2019;Sukmanasa et al, 2017). The digital comic media is needed to be developed (Dwiasih & Agung, 2021;Eva et al, 2020). It can be concluded that E-comic media can facilitate students in learning so that it impacts increasing student understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The development of digital comic media shows that the development of digital comic media is needed especially to support social studies learning (Sukmanasa et al, 2017;Taufiq et al, 2020). The development of effective comic media as teaching materials can increase students' enthusiasm in learning so that it has an impact on student learning outcomes (Dwiasih & Agung, 2021;Enteria & Casumpang, 2019;Eva et al, 2020;Ntobuo et al, 2018). An e-comic is a series of pictures put into a box containing the entire story series (Hobri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%